Analysis of P2 Service Standards in Diarrhea Incidents Toddlers - Awaludin, Akbar Nanda; Aziza, Nurul; Hermawan, Nursefa Arief (Proceedings of the International Conference on Nursing and Health Sciences, 2024)
In 2021, diarrhea services in Pesawaran Regency, Lampung Province, ranked 9th among 15 provinces, with 1,304 cases reported and a service coverage of only 14.5%. A pre-survey at UPT Gedong Tataan Health Center showed that toddler diarrhea service coverage was low, decreasing from 14.24% in 2020 to 7.05% in 2021. Objective: This study aims to assess the service flow of the P2 diarrhea program for toddlers in the working area of UPT Gedong Tataan Health Center, Pesawaran Regency, in 2023. Method: A qualitative descriptive approach was employed to gather detailed insights into the program's implementation. Results: The findings indicate that the P2 diarrhea program for toddlers at UPT Puskesmas Gedong Tataan is not functioning optimally. The screening system, counseling, and health promotion activities are not regularly scheduled, leading to low community awareness and knowledge among mothers of toddlers with diarrhea. Additionally, the diarrhea incident reporting system is inadequate and primarily reactive to outbreaks rather than proactive. Conclusions: To enhance the effectiveness of the P2 diarrhea program for toddlers, it is crucial to improve the scheduling of health education initiatives and strengthen the reporting and screening systems. This will help increase community engagement and knowledge, ultimately reducing the incidence of diarrhea among toddlers.